1996
DOI: 10.1080/00288233.1996.9513193
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 15 ram breeds for export lamb production 2. Proportions of export cuts and carcass class

Abstract: The proportions of cuts from 7885 lamb carcasses sired by 15 different ram breeds, reared on pasture at two locations over 10 years, were measured and examined for breed differences. Although highly significant breed differences were found, their magnitude was small reaching a largest difference between crosses of 1.22% for the leg and 1.26% for the loin compared at the same carcass weight. Compared at the same time of slaughter (age), the maximum differences between the progeny of different ram breeds were 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Essa semelhança está associada ao porte dos ovinos estudados, próximos ao dos Morada Nova. Kirton et al (1996) reportaram que também ocorrem pequenas variações nas proporções dos cortes quando são realizados no mesmo ponto anatômico.…”
Section: Resultsunclassified
“…Essa semelhança está associada ao porte dos ovinos estudados, próximos ao dos Morada Nova. Kirton et al (1996) reportaram que também ocorrem pequenas variações nas proporções dos cortes quando são realizados no mesmo ponto anatômico.…”
Section: Resultsunclassified
“…No differences (P > 0.05) were found between breeds for loin and chump percentages. Kirton et al (1996), in a study with 15 different breeds, also found a higher percentage of leg in Suffolk lambs. These results seem to confirm the superiority of Suffolk breed to develop higher proportions of expensive joints.…”
Section: Carcass Compositionmentioning
confidence: 97%
“…Rams were sampled from the main sources representing the various breeds used in New Zealand and most rams were used for only one year with about 10% used for a second year at the other location to link the genetic results from this trial (Kirton et al 1995(Kirton et al , 1996 together. Their management and the composition data collected have been described previously (Kirton et al 1995(Kirton et al , 1996. All lambs were slaughtered at the same abattoir by mainly the same staff using the same slaughter and carcass dressing methods over the 10 years of the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Carcass measurements were taken as described by Kirton et al (1995Kirton et al ( , 1996 and included longissimus muscle width (A), depth (B), and cross sectional area (eye muscle area) when sectioned between the loin and rack and the fat depth over the longissimus muscle (C) and over the rib (J) as described by Palsson (1939). Two subcutaneous fat depths (S1 and S2) were taken on the cut surface of the shoulder separated between the 5th and 6th ribs and two leg subcutaneous fat depths (LI and L2) were taken on the cut surface of the short leg removed by a cut between the last cervical and first lumbar vertebrae as described by Kirton et al ( 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation